LINGUOCULTUREMES ARE LANGUAGE UNITS WHICH CARRY CULTURAL INFORMATION (Academicia Globe: Inderscience Research, 2021)
The article studies linguoculturemes as language units which carry cultural information and analyze the idioms with eye etalon